The Influence of Board Characteristics on Carbon Emission Disclosure in Indonesia and Malaysia - Selvin Arsya Karunia; Fitrarena Widhi Rizkyana (Owner : Riset dan Jurnal Akuntansi, 2026)
The primary objective of this research is to investigate the extent to which specific attributes of the board of directors affect Carbon Emission Disclosure (CED) practices within energy firms across Indonesia and Malaysia. The research population comprises all energy companies listed on the Indonesia Stock Exchange and Bursa Malaysia during the period 2022–2024. Using a purposive sampling method, the samples were selected based on specific criteria, primarily the accessibility of sustainability and annual reports and the completeness of the data required for the analysis, resulting in 119 firm-year observations. This study adopts a quantitative approach and employs multiple linear regression to analyze the effects of foreign board members, female board members, board expertise, and board educational background on CED. Data analysis was conducted using SPSS version 24, preceded by descriptive statistics and classical assumption tests. The results indicate that board characteristics jointly have a significant effect on Carbon Emission Disclosure. To some extent, female board members, board expertise, and board educational background have a positive and significant influence on the depth and measurability of carbon emission disclosure. In contrast, the presence of foreign board members shows a positive but insignificant effect on CED. These findings imply that variations in Carbon Emission Disclosure are more strongly driven by board attributes closely related to monitoring capacity and internal reporting processes. This study concludes that strengthening internal board characteristics is crucial for enhancing the quality of Carbon Emission Disclosure in energy-sector companies in Indonesia and Malaysia.